Is Healthy Neuroticism Associated with Chronic Conditions? A Coordinated Integrative Data Analysis - Sara J. Weston; Eileen K. Graham; Nicholas A. Turiano; Damaris Aschwanden; Tom Booth; Fleur Harrison; Bryan D. James; Nathan A. Lewis; Steven R. Makkar; Swantje Mueller; Kristi M. Wisniewski; Tomiko Yoneda; et al. (Collabra: Psychology, 2020)
Early investigations of the neuroticism by conscientiousness interaction with regards to health have been promising, but to date, there have been no systematic investigations of this interaction that account for the various personality measurement instruments, varying populations, or aspects of health. The current study – the second of three – uses a coordinated analysis approach to test the impact of the neuroticism by conscientiousness interaction on the prevalence and incidence of chronic conditions. Using 15 pre-existing longitudinal studies (N > 49,375), we found that conscientiousness did not moderate the relationship between neuroticism and having hypertension (OR = 1.00,95%CI[0.98,1.02]), diabetes (OR = 1.02[0.99,1.04]), or heart disease (OR = 0.99[0.97,1.01]). Similarly, we found that conscientiousness did not moderate the prospective relationship between neuroticism and onset of hypertension (OR = 0.98[0.95,1.01]), diabetes (OR = 0.99[0.94,1.05]), or heart disease (OR = 0.98[0.94,1.03]). Heterogeneity of effect sizes was largely nonsignificant, with one exception, indicating that the effects are consistent between datasets. Overall, we conclude that there is no evidence that healthy neuroticism, operationalized as the conscientiousness by neuroticism interaction, buffers against chronic conditions.
Keywords: 330; healthy neuroticism; conscientiousness; chronic condition; health; coordinated analysis; longitudinal